Tropical Endophytic Fungi: Current Knowledge and Perspectives - Miguel A. Gamboa-Gaitán (Acta Biológica Colombiana, 2006)
Endophytic microorganisms are symptomless inhabitants of plant tissues. This group is receiving a growing attention due to its potential in fields as varied as agronomy and medicine. Some more basic aspects of science, such as ecology of communities and plant-microbe interactions have also been studied in this group. This review emphasizes on current literature about tropical endophytes and work in this theme is compared with those developed in temperate zones when appropriate. The most important ecological aspects of this system are discussed, and recommendations about the future directions of research in this field are done, especially those related to the use of endophytes as a model group in modern biology.